2020
DOI: 10.1021/acsami.9b22610
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Curable, Covalently Immobilized Coating for Clinically Relevant Surfaces That Can Kill Bacteria, Fungi, and Influenza Virus

Abstract: Microbial attachment and subsequent colonization onto surfaces lead to the spread of deadly community-acquired and hospital-acquired (nosocomial) infections. Cationic polymeric coatings have gained enormous attention to tackle this scenario. However, non-biodegradable cationic polymer coated surfaces suffer from accumulation of microbial debris leading to toxicity and consequent complexities. Synthetic reproducibility and sophisticated coating techniques further limit their application. In this present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 40 publications
1
47
0
2
Order By: Relevance
“…Nanosized covalent coatings based on quaternary benzophenone-based esters and quaternary benzophenone-based amides cross-link on surfaces when exposed to UV radiation [ 16 ]. In this study, microbes, including drug-resistant pathogens, underwent incapacitation on contacting these nanosized coatings, with 100% inhibition achieved for influenza virus.…”
Section: Self-cleaning Materials and Coronavirus Disease 2019mentioning
confidence: 99%
“…Nanosized covalent coatings based on quaternary benzophenone-based esters and quaternary benzophenone-based amides cross-link on surfaces when exposed to UV radiation [ 16 ]. In this study, microbes, including drug-resistant pathogens, underwent incapacitation on contacting these nanosized coatings, with 100% inhibition achieved for influenza virus.…”
Section: Self-cleaning Materials and Coronavirus Disease 2019mentioning
confidence: 99%
“…The activity of the surfaces was tested following our previously published protocol. [19] Clinically isolated drug-resistant strains of MRSA and E. coli, namely MRSA R3545 and E. coli R3336 were grown in nutrient broth for 6 h at 37°C with constant shaking to obtain mid-log phase bacterial cells. The bacterial solutions were then diluted in saline to attain a cell concentration of ~ 10 6 CFU/mL.…”
Section: Against Planktonic Cellsmentioning
confidence: 99%
“…[16] Several groups have developed covalent grafting techniques to attach antimicrobial polymers comprising quaternary ammonium moeities to different surfaces. [17][18][19] In another approach, researchers have developed an alternative method to coat surfaces through physical deposition or non-covalent attachment of cationic polymers. [20][21][22][23][24][25] Our group has reported the development of an organo-soluble, hydrophobic, quaternary polyethyleneimine (PEI)-based antimicrobial paint.…”
Section: Introductionmentioning
confidence: 99%
“…Human infections (almost 80%) can be transmitted through contaminated surfaces to bacterial, fungi, and viral. Especially during the COVID-19 epidemic, it is necessary to provide antimicrobial coatings to control and prevent its spread [ 28 ]. On the other side, hospital infections are a threat to global healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…So far, polymeric systems for the preparation of coatings, membranes, and surfaces to fight against bacteria, viral, and fungi have been widely reported. Here are some of the latest developments: Haldar et al [ 28∗ ] reported an antimicrobial covalent coating to kill bacteria, fungi, and influenza viruses on clinical surfaces. For this aim, using UV irradiation, water-soluble quaternary benzophenone-based ester and amide were covalently immobilized on surpasses such as cotton sheets and polyurethane via dip-coating and drop-casting methods.…”
Section: Introductionmentioning
confidence: 99%